1988
DOI: 10.1056/nejm198811243192103
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Treatment of Neonatal Alloimmune Thrombocytopenia

Abstract: Neonatal alloimmune thrombocytopenia results from the formation of a maternal antibody to a paternal antigen on fetal platelets. Intracranial hemorrhage, which may be antenatal, occurs in approximately 15 to 20 percent of infants with this form of thrombocytopenia. In families with an affected infant, 75 percent of subsequent infants are affected. We report the results of antenatal treatment with intravenous gamma globulin, with or without dexamethasone, in seven pregnant women who had previously had infants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
156
0
8

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(167 citation statements)
references
References 30 publications
3
156
0
8
Order By: Relevance
“…3 Administration of intravenous immunoglobulin (IVIG) to the mother, initially given in conjunction with dexamethasone, was first used to prevent recurrence of antenatal intracranial hemorrhage in 1988. 4 This approach of providing IVIG-based medical therapy administered to the mother to increase the fetal platelet count has since been extensively investigated in hundreds of maternal-fetal pairs. 5 The efficacy of IVIG-based therapy has been supported by numerous studies [6][7][8][9][10][11][12][13][14][15][16] (Table 1A) but not by others [17][18][19] (Table 1B).…”
Section: Financial and Other Disclosures Provided By The Authors Usinmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Administration of intravenous immunoglobulin (IVIG) to the mother, initially given in conjunction with dexamethasone, was first used to prevent recurrence of antenatal intracranial hemorrhage in 1988. 4 This approach of providing IVIG-based medical therapy administered to the mother to increase the fetal platelet count has since been extensively investigated in hundreds of maternal-fetal pairs. 5 The efficacy of IVIG-based therapy has been supported by numerous studies [6][7][8][9][10][11][12][13][14][15][16] (Table 1A) but not by others [17][18][19] (Table 1B).…”
Section: Financial and Other Disclosures Provided By The Authors Usinmentioning
confidence: 99%
“…3 In humans, at least some of these B cells produce known autoantibodies. 4 Our laboratory has previously shown that Y chromosome-encoded minor histocompatability antigens elicit specific antibody responses following sex-mismatched hematopoietic stem cell transplantation, and the presence of these allo-antibodies correlates with the development of chronic GVHD. 5,6 Patients with minor histocompatability antigen-specific antibodies have also been found to have alloreactive CD4 + T cells directed against different epitopes derived from the same protein 7 but the pathogenicity of these antibodies remains unproven.…”
mentioning
confidence: 99%
“…In contrast, maternal alloantibodies developed against a fetal platelet alloantigen inherited from the father, induce a severe fetal TP but is associated with normal maternal platelet counts. TP in the thus affected fetus may occur as early as 18 th week of gestation and carries the risk of severe antenatal cerebral hemorrhage and/or porencephaly warranting specific antenatal management [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Often, the diagnosis cannot be made until after the first affected child, although sometimes pregnancies at risk are identified when female siblings of an affected mother are tested for platelet type. Once recognised, weekly administration of immune globulin intravenously beginning at 20 weeks of gestation has been shown to stabilise or increase the fetal platelet count and reduce the risk of bleeding in most affected fetuses 18,19 . The place of corticosteroids is unclear.…”
Section: Discussionmentioning
confidence: 99%